Pembuatan Biodisel dari Ampas Kelapa dengan Metode Transesterifikasi In-Situ dan Katalis Kalsium Oksida - Afriando Ryan Maulana; Tutik Muji Setyoningrum (Eksergi, 2019)
Biodiesel is an alternative fuel for diesel engine that attracts the world attention. Indonesia is one of the biggest coconut producers in the world. Coconut meat waste is known to still contain up to 24% wt of vegetable oil. The potential of this coconut waste can be used for producing biodiesel that has economical value. This research uses coconut waste as the main raw material. The biodiesel production process is carried out by in-situ transesterification method with methanol as the solvent and reactant; and calcium oxide powder as the catalyst. The catalyst is activated by stirring and heating in methanol. The oil percentage in the coconut waste obtained from soxhletation is 20 % wt. The ratio of methanol to coconut waste of 12.5:1 (v/w) and catalyst to coconut waste of 3.5 % wt results the biodiesel yield of 96.43 % mol. The biodiesel flash point at this variable is 116 °C. This value has met the Badan Standar Nasional (BSN) standard